A Comparative Analysis of the Intensifiers Quite, Rather, and Pretty Used by Americans and British People: A Corpus Study - Rex Stardy (Universitas Bunda Mulia, 2019)
Words have many different meanings and this can cause problems for nonnative speakers of English. Because words can mean many different things depending on the sentence that they appear in, Indonesian learners of English often have trouble telling the different meanings apart, especially when the words are synonyms or from specific group of words like intensifiers. From this, the writer would like to do a research on the topic of the comparison between American and British English. The research is limited to comparing the intensifiers quite, ratherand pretty. The data is taken from COCA for the American English and BNC for the British English. The result shows that in general, the three intensifiers are more or less similar in meaning, with only slight differences. The usages of these three intensifiers by Americans and British people are also not too different.Keywords: intensifier, American and British people, corpus